Rainwater composition in Athens, Greece - Dikaiakos, J. G.; Tsitouris, C. G.; Siskos, P. A.; Melissos, D. A.; Nastos, P. (Atmospheric Environment - Part B Urban Atmosphere, 1990)
Wet precipitation-only samplers were used to collect wet deposition at two sites in the Athens basin, Greece for the period March 1986 - February 1987. Concentrations of major cations (H +, NH 4 +, Na +, K +, CA 2+) and major anions (Cl -, NO 3 - and SO 4 2-) were determined for the first time in rainwater samples in Greece. Bicarbonate concentrations were calculated. The relative importance of natural and anthropogenic sources were estimated by a chemical balance. The majority of rain collected has a neutral or alkaline character. Acidity was due to the presence of H 2SO 4 and HNO 3. The statistical analysis of the correlation between the concentration of chemical species confirm the influence of natural and anthropogenic sources. In all samples, SO 4 2- concentrations exceed NO 3 - concentrations exceed NO 3 - concentrations despite the dominance of low S oil burning in the region. The wet flux of S was calculated to be 0.34 g m -2 a -1.
Keywords: acid; acid precipitation; acid rain; air sampling; article; Greece; rain; Wet deposition